1990
DOI: 10.1038/ki.1990.168
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase inhibition potentiates the renal actions of atrial natriuretic factor

Abstract: Atrial natriuretic factor (ANF) is degraded by neutral endopeptidase. We hypothesized that neutral endopeptidase inhibition (NEP-I) increases sodium excretion and that this effect would be potentiated in the presence of an isolated increase in intrarenal ANF. In seven anesthetized dogs, ANF was infused into one renal artery to produce pathophysiologic concentrations in the supplemented kidney while the control kidney received physiologic circulating concentrations of ANF. In the control kidney, NEP-I (SQ 28,60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 22 publications
1
19
1
1
Order By: Relevance
“…Although some authors have questioned the ability of augmented tubular ANF concentration to promote natriuresis [20], our findings are consistent with those of others who have postulated that neutral endopeptidase inhibi tion confers a protective effect to filtered ANF. allowing enhanced distal delivery of the peptide to medullary col lecting ducts where the natriuretic action of the peptide is effected [ 19]. Support for this hypothesis comes from a rat model of CHF.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although some authors have questioned the ability of augmented tubular ANF concentration to promote natriuresis [20], our findings are consistent with those of others who have postulated that neutral endopeptidase inhibi tion confers a protective effect to filtered ANF. allowing enhanced distal delivery of the peptide to medullary col lecting ducts where the natriuretic action of the peptide is effected [ 19]. Support for this hypothesis comes from a rat model of CHF.…”
Section: Discussionmentioning
confidence: 56%
“…Previous work has documented that most cGMP found in the urine is synthesized in the kidney [17], and that cGMP production specifically reflects ANF activity [ 1,18], Consequently, candoxatril appears to have a pref erential renal effect leading to natriuresis, an effect pre viously postulated with other neutral endopeptidase in hibitors, to be mediated at the level of the renal tubules [7,19]. Although some authors have questioned the ability of augmented tubular ANF concentration to promote natriuresis [20], our findings are consistent with those of others who have postulated that neutral endopeptidase inhibi tion confers a protective effect to filtered ANF.…”
Section: Discussionmentioning
confidence: 99%
“…Although NEP degrades numerous peptides in vitro, a smaller number have been shown to be inactivated by this enzyme in vivo, including enkephalins, substance P, bradykinin and atrial natriuretic factor (ANF) [1]. With the discovery that NEP inactivates ANF [3] and that NEP inhibition potentiates the renal actions of ANF [4], much interest has been generated in charac-terizing the distribution, function and regulation of NEP in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that NEP inhibition in control animals and in severe CHF is not associated with an increase in GFR despite significant natriuretic actions. 5,12 Thus, the enhanced GFR response to acute NEP inhibition in mild CHF was unexpected. One may conclude that the increase in GFR associated with an increase in RBF suggests that acute NEP inhibition resulted in afferent arteriolar dilatation with an increase in glomerular hydrostatic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, severe CHF is known to be a state of renal hyporesponsiveness to ANP, in part due to the opposing renal actions of the RAAS. 5,6 Neutral endopeptidase 24.11 (NEP) is a metalloprotease that is localized in the greatest abundance in the kidney and degrades natriuretic peptides such as ANP. NEP inhibition has emerged as a therapeutic strategy in the management of CHF through potentiation of the renal natriuretic and renininhibiting actions of ANP.…”
mentioning
confidence: 99%